CYTOTOXICITY OF NON-BOUND COLICINS EXTRACTED FROMEscherichia coil ON NORMAL WHITE BLOOD CELLS ANDMYELOBLAST ISOLATED FROM ACUTE MYELOID LEUKEMIABLOOD PATIENTS - Obaid, Hind; Essa, Rajwa; Yaseen, Nahiy (Iraqi Journal of Science, 2024)
Four types of non-bound colicins (H٥, H٩, H١٣, H١٩) were extracted fromintestinal normal flora Escherichia coil isolated from healthy people’s stool. Thenstudy cytotoxic effect of colicins on normal white blood cells (WBCs) from healthypeople. And cytotoxicity on myeloblasts isolated from AML patients blood. Resultsshowed, myeloblasts from AML patients were more sensitive to colicins thannormal WBCs from healthy people.The toxic effect was dose-dependent andexposure time.